Solving Yin-Yang Puzzles Using Exhaustive Search and Prune-and-Search Algorithms - Putra , Made Indrayana; Arzaki , Muhammad; Wulandari, Gia Septiana ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
We investigate some algorithmic and mathematical aspects of Yin-Yang/Shiromaru-Kuromaru puzzles. Specifically, we discuss two algorithms for solving arbitrary Yin-Yang puzzles, namely the exhaustive search approach and the prune-and-search technique. We show that both algorithms have an identical asymptotic running time of O(maxmn, 2^(mn−h)) for finding all solutions of a Yin-Yang instance with h hints of size m x n. Nevertheless, our experiments show that the practical running time of the prune-and-search technique outperforms the conventional exhaustive search approach.